Global, regional, and national burdens of facial fractures: a systematic analysis of the global burden of Disease 2019 - Ze-Xing Zhang; Long Xie; Zhi Li (BMC, 2024)
Abstract Background The incidence of facial fractures has undergone tremendous changes in recent years as a result of socio-economic development and aging populations. Currently, there is a lack of updated and comprehensive analyses of global trends and causes of facial fractures. The Global Burden of Disease (GBD) database is a product of a global research organization used to quantify the global impact of hundreds of diseases, injuries, and risk factors. The aim of this study was to update global burden of facial fractures from 1990 to 2019 by using the GBD2019. Materials and methods The present study extracted the global incidence, prevalence, and years lived with disability (YLDs) for facial fractures, as well as the age-standardized rates (ASRs) of these variables using the Global Burden of Disease (GBD) 2019 database. The estimated annual percentage change (EAPC) was used to assess the trends of ASRs. Results Between 1990 and 2019, the incidence of facial fractures increased from 8,943,707 to 10,676,340, but the age-standardized incidence rate (ASIR) decreased from 161.5 to 138.8 per 100,000. Prevalence and YLDs exhibited the same trend as incidence. Over the 30 years, the incidence of facial fractures was consistently greater in males than in females. However, females aged ˃ 75 years had higher fracture incidence rates than males aged ˃ 75 years in 2019. The leading cause of facial fractures was falls, and both the age-standardized prevalence rate (ASPR) and age-standardized years lived with disability rate (ASYR) of falls increased with age. Conclusion Facial fractures still represent a significant burden to the world. Incidence, prevalence and YLDs all showed increasing trends, while ASRs decreased gradually from 1990 to 2019. Enhancing the quality of facial fractures data is helpful for monitoring the burden of facial fractures.